The Movement-Image Compatibility Effect: Embodiment Theory Interpretations of Motor Resonance With Digitized Photographs, Drawings, and Paintings - Casper, Mark-Oliver; Nyakatura, John A.; Pawel, Anja; Reimer, Christina B.; Schubert, Torsten; Lauschke, Marion (Frontiers in Psychology, 2018)
To evoke the impression of movement in the “immobile” image is one of the central motivations of the visual art, and the activating effect of images has been discussed in art psychology already some hundred years ago. However, this topic has up to now been largely neglected by the researchers in cognitive psychology and neuroscience. This study investigates – from an interdisciplinary perspective – the formation of lateralised instances of motion when an observer perceives movement in an image. A first step was to identify images that evoke a perception of movement in a certain direction and to give this a rating. Reaction times leading to the engagement of a joystick following the presentation of images are used to evidence the postulated movement occasioned by the perception of movement in an image. Where the required direction of joystick moves matched the expected perception of movement direction in the image, considerably shorter reaction times were recorded. The experiment was able to prove a “movement-image compatibility effect” in observers of images. Based on this, the paper revisits and brings up to date the theses on motor sensory response to images which were developed in art psychology at the beginning of the 20th century. It furthermore contributes an embodiment theory interpretation to the prevalent representational explanation of compatibility effects.